Gerakan dan Modernisasi Pendididkan Islam - Jumi Romelah; M. Nurul Humaidi (Civiliza Publishing, Indonesia., 2026)
This article examines the movement and modernization of Islamic education as a response to the backwardness of the Muslim community caused by static thinking (jumud) and the practice of taqlid. The study employs a library research method with content analysis of literature from the past ten years. The findings indicate that the modernization of Islamic education is understood as a process of renewing paradigms and educational systems aimed at improving the quality of education, in line with the meaning of reform. There are three main patterns of modernization: orientation toward Western educational systems, orientation toward the purification of Islamic teachings, and orientation toward the cultural wealth of each nation with a spirit of nationalism. Reformist figures such as Muhammad Abduh, Jamaluddin al-Afghani, and Ahmad Dahlan played an important role in integrating Islamic values with modern needs. The challenges of modernization in the digital era include value secularization, moral crises, cultural globalization, as well as limited digital literacy and educational infrastructure. This article emphasizes that the modernization of Islamic education is a necessity to maintain the relevance of Islamic teachings while responding to the demands of the times.